Identifying of the reasons for the project design errors in the portuguese construction industry - Couto, J. Pedro (2012)
The European construction industry is currently experiencing great difficulties and challenges but in Portugal the sector is facing a critical moment which will decisively impact its future. Along with the redefinition of its legal framework, so as to make it more efficient and bring it up to date, the sector is going through stagnation in the private market and a slump in the public construction market, mostly on account of the current state of economy country. Furthermore, the lack of accomplishment of cost, time, safety, and quality, has been recurrently mentioned in the press and in technical literature as one of the main causes for the lack of competitiveness of sector. The poor quality of project designs has been considered as main reason for the recurrent time and cost overruns. Previous studies have often found that designs contain a lot of errors and omissions. This paper wills critically to discuss the problem of poor quality design in Portugal using literature and data from a set of interviews with expert construction managers. The main reasons for the poor quality of project designs have been established from the outcomes of a national survey undertaken and a series of interviews of experts. Some measures that would lessen the problem have been identified.